Mechanics of intact bone marrow. (October 2015) - Jansen, Lauren E.; Birch, Nathan P.; Schiffman, Jessica D.; Crosby, Alfred J.; Peyton, Shelly R.
Abstract: The current knowledge of bone marrow mechanics is limited to its viscous properties, neglecting the elastic contribution of the extracellular matrix. To get a more complete view of the mechanics of marrow, we characterized intact yellow porcine bone marrow using three different, but complementary techniques: rheology, indentation, and cavitation. Our analysis shows that bone marrow is elastic, and has a large amount of intra- and inter-sample heterogeneity, with an effective Young׳s modulus ranging from 0.25 to 24.7 kPa at physiological temperature. Each testing method was consistent across matched tissue samples, and each provided unique benefits depending on user needs. We recommend bulk rheology to capture the effects of temperature on tissue elasticity and moduli, indentation for quantifying local tissue heterogeneity, and cavitation rheology for mitigating destructive sample preparation. We anticipate the knowledge of bone marrow elastic properties for building in vitro models will elucidate mechanisms involved in disease progression and regenerative medicine. Graphical abstract: Highlights: Bone marrow is a benign material with a large amount of intra- and inter-tissue heterogeneity. The E Eff of intact porcine marrow ranges from 0.3 to 24.7 kPa at physiological temperature. Bulk rheology is the best method to capture the effects of temperature on tissue viscoelasticity. Indentation is the ideal method for quantifying local tissue heterogeneity. Cavitation mitigates destructive sample preparation, so tissue mechanics can be tested in situ .